Histological change in Biomphalaria glabrata, Say, 1817, Schistosoma mansoni intermediary host, submitted to Niclosamide - Pile, Edwin Alberto Maure; Pastor, Nanci; Santos, José Augusto dos; Barros, Juliana SãoLuiz de (Brazilian Journal of Veterinary Research and Animal Science, 2002)
It was realized a histological evaluation of Biomphalaria glabrata submitted to aqueous solutions of niclosamide, in concentrations subletais. The experiments were accomplished in agreement with the parameters described by World Health Organization for tests with moluscicidas. The results demonstrated focal lesions in the digestive gland, kidney and gonads, and a correlation between the solution concentration and the damage level.